Propuesta de un sistema de gestión Ambiental basado en la Norma ISO 14001:2015 para la empresa pesquera HAYDUK S.A. - Vera Burgos, Roxana Elizabeth (2018)
ABSTRACT The objective was to formulate a proposal for an environmental management system based on the ISO 14001: 2015 standard for the fishing company HAYDUK S.A, Methodologically, the research work is applied, where the personnel of the fishing company HAYDUK S.A. conformed by 77 people. A comparative study of the compliance of the guidelines of the international standard with what was currently being developed in the company HAYDUK S.A. The environmental impacts that participate in the processes were identified. A quantitative study was carried out through a survey addressed to workers of company HAYDUK S.A. Among the main results, it should be noted that there is a 60% negative perception of the environmental management system within the company; in addition to a level of 23% qualified as low compliance with the guidelines of IS014001. The environmental management policy was elaborated; the environmental impacts were identified; the most significant environmental ones were identified, such as the consumption of electricity, water consumption, the generation of solid waste, the generation of noise and the generation of gases and vapors. Finally, it was concluded that to minimize potential environmental impacts, the fishing company HAYDUK S.A., should implement and maintain the environmental management system; which establishes a structured, orderly, integrated and logical sequence to achieve environmental objectives and goals.